Poor initiation of smoking cessation therapies in hospitalised patients with chronic obstructive pulmonary disease is associated with low levels of formal training among hospital doctors and under‐utilisation of nursing‐led interventions. Issue 11 (20th November 2020) - Pham, Jonathan; Pitney, Stephanie; Sweeney, Duncan; Reekie, Clive; Harkness, Nick
Abstract: Background: Smoking cessation intervention is a key component in the management of chronic obstructive pulmonary disease (COPD). Aims: To evaluate the prescribing of smoking cessation therapies (SCT) among hospital clinicians and identify factors that may hinder delivery of effective interventions. Methods: A retrospective analysis of medical records of patients admitted to the Royal Hobart Hospital with an acute exacerbation of COPD was performed. A survey of hospital clinicians was also performed to ascertain levels of training and confidence in prescribing SCT. Results: Nearly all medical and non‐medical hospital clinicians self‐reported confidence in offering SCT (91.1 vs 82.5%, respectively, P = 0.216). However, of the 122 eligible patients in our study population, the majority did not have any form of SCT initiated during their admission ( n = 68, 55.7%) and only 21 patients (17.2%) were referred to the nurse‐led smoking cessation service. Very few patients were initiated on efficacious regimes such as combination‐nicotine replacement therapy ( n = 8, 6.6%) or varenicline ( n = 2, 1.6%). Only a small proportion of hospital doctors reported confidence in prescribing varenicline and bupropion (17.2 and 6.9%, respectively). Furthermore, very few hospital doctors reported ever receiving formal training in SCT compared to non‐medical hospital staff (42.2 vs 84.5%, P < 0.001). Conclusion: Our study highlights the real‐life challenges in tackling nicotine dependence in hospitals: under‐utilisation of evidence‐based pharmacotherapies, limited access to formal training for doctors and poor uptake of nurse‐led smoking cessation services. Granting limited prescribing rights for specialised nurses may help hospital clinicians to alleviate gaps in current clinical practice.